PENINGKATAN EFEKTIVITAS PENYELESAIAN SENGKETA MEDIS MELALUI ALTERNATIF NON-LITIGASI (MEDIASI DAN ARBITRASE) PASCA PENERAPAN UU NO. 17 TAHUN 2023 - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2025)
Medical disputes are one of the most important issues in the world of healthcare, often giving rise to legal, ethical, and social implications for both medical personnel and patients. The implementation of Law No. 17 of 2023 on Health has brought significant changes to the resolution of medical disputes by mandating non-litigation resolution through mediation or arbitration mechanisms before bringing the matter to court. This study aims to analyse the effectiveness of mediation and arbitration as alternative dispute resolution mechanisms following the implementation of the aforementioned law, as well as to identify the challenges and supporting factors for their implementation. The research method employed is a normative-empirical legal approach using a qualitative literature review. The results of the study indicate that non-litigation dispute resolution mechanisms have several advantages, including a faster process, cost-effectiveness, and a focus on restorative justice principles. However, their implementation still faces various challenges, such as low public awareness, a limited number of competent mediators and arbitrators in the medical field, and insufficient infrastructure and technical regulations for implementation. Therefore, collaborative efforts between the government, medical institutions, professional organisations, and the public are needed to strengthen the out-of-court medical dispute resolution system optimally.